Utilization of Mango (Mangifera indica L. c.v. Carabao) kernel flour as wheat flour substitute for cake formulation - Satinitigan, Shaina T. (College of Home Economics, University of the Philippines Diliman, 2023)
This study aimed to utilize mango (variety: Carabao) kernel flour as a wheat flour substitute for cake formulation to help resolve environmental concerns on mango processing byproducts and meet the increasing demand for flour for bakery products. Mango kernel flour (MKF) was produced through sun evaporation and oven drying. Proximate analysis showed that the developed MKF had 45.6 ± 0.02 moisture, 4.64 ± 0.03 crude protein, 6.58 ± 0.08 crude fat, 1.04 ± 0.01 crude ash, 3.19 ± 0.11 crude fiber, and 42.1 percent carbohydrates. It is higher in moisture, crude ash, crude fat, and crude fiber content but lower in crude protein and carbohydrate content than wheat flour. The developed MKF partially substituted wheat flour at levels 0, 10, 20, and 30 percent in cake formulation. Regarding physical properties, as MKF substitution increased, the cakes’ height decreased. Meanwhile, MKF substitution did not significantly affect the weight of the cakes. Results from the consumer acceptability test using a completely randomized design (n=40) revealed that there was no significant difference (p<0.05) among all treatments in all sensory attributes. Hedonic test scores ranged from 7.1-8.2 (like to like very much) across all sensory attributes, implying that the cakes partially substituted with MKF at different levels are highly acceptable. This study can be used as a basis for further studies on the utilization of Carabao mangoes to develop MKF, specifically for cake formulation, and comparison with MKF developed using other mango varieties.